PROPERTY AND ALLOWANCE RIGHTS OF MILITARY PERSONNEL: BASED ON HISTORICAL SOURCES (Eureka Journal of Education & Learning Technologies, 2026)
The article analyzes the property and allowance rights of military personnel and their social protection based on historical sources. Using the examples of the Code of Hammurabi, Roman law, the Avesta, and the Khwarazmian state, the historical foundations of granting land to soldiers, providing material incentives, and strengthening their social status are revealed.
Keywords: Military personnel, property rights, financial allowance, social protection, historical sources